Exploring Barriers to Interprofessional Collaboration in Public Health Centres in Palu, Indonesia - Hasri Ainun Syawal; Rina Masadah; Firdaus Hamid; Bau Dilam Ardyansyah; Ichlas Nanang Afandi; Muhammad Idham Rahman (Education in Medicine Journal, 2026)
Interprofessional collaboration (IPC) is an important part of the innovation strategy to overcome the health professional crisis. Most health professionals who currently work at public health centres engage in IPC without receiving training or collaborative learning experience at the undergraduate level, namely interprofessional education (IPE). This study aimed to determine the challenges ofinterprofessional health collaboration at public health centres in Palu. The researchers purposively visited 10 general practitioners to explore IPC interactions that occurred at their public health centres in Palu by conducting in-depth interviews. This study highlighted that the challenges of IPC at public health centres in Palu included a lack of roles and responsibilities, poor service team coordination,misunderstandings in interprofessional communication, and ethical issues in the health professions. Therefore, it is deemed pivotal to promptly implement IPE for undergraduate medical students at Alkhairaat University to help them acquire the skills needed to enter the health workforce and prepare them for IPC.